Motivasi Mahasiswa Usia Dewasa Mengikuti Perkuliahan pada Program Studi Pendidikan Guru Paud di FKIP Uninus Bandung - Agus Ruswandi (PG-PAUD Trunojoyo, 2018)
This research is based on data from observation data of students of PG PAUD Uninus Bandung, which in conclusion about 40% of students of PG PAUD study program from the age side including middle age or other term is included in middle age. This condition attracts the attention of researchers so it is important to examine the background of students, motivation, goals and reasons of the students of the adult age group to attend the lectures in the PG PAUD Uninus FKIP. It is expected to obtain data for the stakeholders both at the level of Prodi, Faculty and University level. The method used in this research use descriptive analytical research method with qualitative approach. This method is supported by data collection techniques such as observation, documentation and interviews. The sample of this research is students of PG PAUD Uninus FKIP study program which is in the adult age range or about 25 and up to 60 years old. Technique of data analysis this research use three step analysis, that is data reduction, data display and data verification. The expected output of this research is in the form of scientific articles published in accredited national journals. The results showed that adult students who attended lectures at Prodi PG PAUD mostly aged between 51 to 55 years from the employment side of most of the students is a non-civil servant or honorary teachers and most have not been certified. adult students attending or continuing lectures in Prodi PG PAUD, among others, because the demands of their professions as PAUD teachers for the benefit of linearity or for students who have not previously had a diploma equivalent to some other scholars who have civil servants but the diploma is not linear with PAUD so that they have to go to college or PAUD field so that the diploma in accordance with the profession. The results conclude that economic factors are not the dominant factor for students to follow or continue their lectures in the area of early childhood is more dominated by linearity with their work not because of economic factors. As for economic reasons, certification. or civil servants that only a small part of one of the factors of adult students continue studying in Prodi PG PAUD.